2019
DOI: 10.24874/pes01.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Nanoparticles in Palm Oil Olein as Solid Additives

Abstract: Palm oil olein and palm oil ester is well-known potential candidate in plant-based oil to replace the conventional mineral oil. Harvested all year round, the advantages and benefits initiate the palm oil to be used in varieties of application. In this paper, palm oil olein was tested on its capability as a lubricant to replace the mineral oil. To enrich the performance of this oil, different types of nanoparticles additives were added. Previous studies proved that by adding small size of additives into lubrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…The triglycerides structure of the vegetable oils, with high viscosity and viscosity index and flash point, make it the best alternative to mineral oil [4]. The excellent lubricating properties also have been proven in past studies, whether without or with presence of dedicated additives [5][6][7][8].…”
Section: Introductionmentioning
confidence: 94%
“…The triglycerides structure of the vegetable oils, with high viscosity and viscosity index and flash point, make it the best alternative to mineral oil [4]. The excellent lubricating properties also have been proven in past studies, whether without or with presence of dedicated additives [5][6][7][8].…”
Section: Introductionmentioning
confidence: 94%
“…Many investigators have reported the thermal enhancement and tribological improvement of mineral and synthetic refrigeration oil and bio lubricants with and without the addition of nanoparticles and concluded that the inclusion of nanoparticles to refrigeration oil leads to the reduction in power consumption, lower friction coefficients and enhancement in COP [14][15][16][17][18]. However, the inclusion of nanoparticles in lubricants, contribute to copious problems such as clogging, sedimentation and erosion and reasons for significant enhancement with nanoparticles at different concentrations are also unclear [19].…”
Section: Introductionmentioning
confidence: 99%